TRAINING PROGRAM MANAGEMENT: STUDY ON HANDMADE TRAINING PROGRAM AT PKBM RUMPUN AKSARA - Setiyani, Gayuh; Hendrawijaya, Arif Tukiman; Hasan, Fuad (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to determine and describe the management of handmade training programs in PKBM Rumpun Aksara. This study uses a descriptive type of research with a qualitative approach. The research site is located in PKBM Rumpun Aksara Panti Jember using a purposive area technique. The technique of determining the informants used purposive sampling. Data collection techniques using observation, interviews and documentation. The technique of checking the validity of the data used was increased persistence, extended observations and triangulation in the form of source triangulation and technical triangulation. Data analysis used the theory of Miles and Hubarman by collecting data, reducing data, presenting data, and verifying data. The results showed that the planning activities in the handmade training in PKBM Rumpun Aksara were carried out in a structured and systematic way, starting from identifying needs, to making learning lesson plans, as well as determining methods and media carried out by the training instructor. The implementation of the handmade training program has been running according to the predetermined plan. Meanwhile, the evaluation activity for the handmade training is holding a meeting with the instructor who discusses the implementation of the program. While the evaluation of the learning community by conducting an assessment of the process, results, level of interest of learning residents and the impact of handmade training for learning residents.